2008
DOI: 10.1105/tpc.108.063487
|View full text |Cite
|
Sign up to set email alerts
|

Starch Granule Biosynthesis in Arabidopsis Is Abolished by Removal of All Debranching Enzymes but Restored by the Subsequent Removal of an Endoamylase

Abstract: Several studies have suggested that debranching enzymes (DBEs) are involved in the biosynthesis of amylopectin, the major constituent of starch granules. Our systematic analysis of all DBE mutants of Arabidopsis thaliana demonstrates that when any DBE activity remains, starch granules are still synthesized, albeit with altered amylopectin structure. Quadruple mutants lacking all four DBE proteins (Isoamylase1 [ISA1], ISA2, and ISA3, and Limit-Dextrinase) are devoid of starch granules and instead accumulate hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
164
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(178 citation statements)
references
References 60 publications
12
164
1
1
Order By: Relevance
“…7,8,and 10). A similar function was recently demonstrated for isoamylase paralogs in Arabidopsis (Streb et al, 2008). The specific roles of HvISA1 and HvISA2 remain unclear (Burton et al, 2002), and neither seems to be under diurnal control (Table I).…”
Section: Diurnal Regulation Of Starch Metabolism and Sugar Signalingsupporting
confidence: 72%
“…7,8,and 10). A similar function was recently demonstrated for isoamylase paralogs in Arabidopsis (Streb et al, 2008). The specific roles of HvISA1 and HvISA2 remain unclear (Burton et al, 2002), and neither seems to be under diurnal control (Table I).…”
Section: Diurnal Regulation Of Starch Metabolism and Sugar Signalingsupporting
confidence: 72%
“…Residual starch granules in ISA1-deficient mutants are abnormal in size, shape, and number and contain structurally altered amylopectin. These observations are remarkably consistent across species and tissues, including maize (Zea mays), rice (Oryza sativa), and barley (Hordeum vulgare) endosperm, potato (Solanum tuberosum) tuber, Arabidopsis (Arabidopsis thaliana) leaf, and Chlamydomonas reinhardtii cells (James et al, 1995;Mouille et al, 1996;Zeeman et al, 1998;Kubo et al, 1999;DauvillĂ©e et al, 2001a;Burton et al, 2002;Bustos et al, 2004;Delatte et al, 2005;Wattebled et al, 2005Wattebled et al, , 2008Streb et al, 2008). Thus, ISA1 and ISA2 appear to have been adapted primarily for activity in starch biosynthesis rather than degradation.…”
mentioning
confidence: 66%
“…Thus, ISA1 and ISA2 appear to have been adapted primarily for activity in starch biosynthesis rather than degradation. The role of these DBEs appears to be remodeling of a soluble glucan precursor by the removal of certain branch linkages, thus facilitating the transition to the semicrystalline state Myers et al, 2000;Streb et al, 2008).…”
mentioning
confidence: 99%
“…First, Streb et al (2008) reported that in a particular mutant background lacking starch DBE, the presence of an additional mutation in a particular plastidial a-amylase restored starch synthesis in Arabidopsis leaves. This may imply that starch granule aggregation could dispense with the postulated debranching mechanism, although the crystallinity of this residual material still needs to be ascertained.…”
Section: Evolution Of Direct Dbes Involved In Amylopectin Maturation mentioning
confidence: 99%